The Black Box Book : Archives and Curatorship in the Age of Transformation of Art Institutions - Horáková, Jana; Kupková, Marika; Szűcsová, Monika; Ghidini, Marialaura; Tedone, Gaia; Hunter, Roddy; Cook, Sarah; Klodner, Michal; Sudmann, Andreas; Trnková, Barbora; Pilka, Lukáš; Sikora, Pavel; et al. (Masaryk University, 2023)
The publication is the result of the efforts of an international collective of authors to capture the transformation of exhibition institutions and curation during the Covid 19 pandemic, with a focus on the year 2020. It seeks an answer to the question of how curatorial strategies, communication platforms and the social function of exhibition institutions have changed under the influence of rapid and external circumstances, that forced transition from physical gallery spaces to online. It critically reflects on the exhibition project Černá skříňka/The Black Box (Galerie TIC), in which several curatorial approaches were applied, including the use of artificial intelligence, and places it in the broad context of curatorial projects that were carried out at the same time at home and abroad as well as in the network of terminology apparatus, which is built around the phenomenon of online curation. The research method is a combination of writing the history of presence, mostly from the pen of direct participants, which lends authenticity and engagement to the texts, with theoretical reflection informed by digital and network media theory.